Przyrzekając niemoc. O duchu i egzystencji - Moryń, Mariusz (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
Presented article concerns existential sources and basis of humanism. The Author presents his own understanding of the title notions and describes human being as weak and incomplete in his essential nature – and whose duty is to hasten his passing. Human is understood as a spirit, existing in space of uncertainty, mystery, mortality, both demanding and somewhat fearsome. Presented considerations include a concept different from phenomenological understanding of human as a pure subject. The Author demonstrates that the theory of the absolute self consciousness is based on absolute misery and oppression.